2004
DOI: 10.1002/biof.552210136
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of tocha, the stems and leaves of Ampelopsis grossedentata, and ampelopsin

Abstract: Hepatoprotective effect of the leaves and stems of Ampelopsis grossedentata together with its main constituent, ampelopsin, were examined on D-galactosamine induced liver injury in rats. The diet containing 50% ethanolic extract (1%) and ampelopsin (0.1%) markedly suppressed the increase of LDH, ALT, AST, alpha-tocopherol levels and GSG/GSSH caused by GalN treatment. These results suggested that ampelopsin from Tocha acted to prevent the oxidative stress in vivo that may have been due to active oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 3 publications
2
54
0
Order By: Relevance
“…As some flavonoids contained in tea and herbs have been found to be effective in preventing liver injury (Wada et al, 2000;Murakami et al, 2004), further investigation of major flavonoids contained in petals of the edible chrysanthemum flower (Chrysanthemum×morifolium Ramat. forma esculentum Makino, c.v Kotobuki) and their physiological functions is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…As some flavonoids contained in tea and herbs have been found to be effective in preventing liver injury (Wada et al, 2000;Murakami et al, 2004), further investigation of major flavonoids contained in petals of the edible chrysanthemum flower (Chrysanthemum×morifolium Ramat. forma esculentum Makino, c.v Kotobuki) and their physiological functions is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Consequently, many physiological functions of flavonoids, such as their preventive effects on cancer, cardiovascular disease, liver injury and oxidative stress, neuroprotective effects, and hypoglycemic effects, have been investigated and reported, [4][5][6][7][8][9][10][11] and the bioavailability, absorption from the gastro-intestinal tract, and metabolism of flavonoids have been examined in relation to their function. [12][13][14] However, few reports have been presented on the precise relationship between the chemical structure of dietary flavonoids and their bioavailability or functions.…”
mentioning
confidence: 99%
“…Among six isolated compounds, compound 1 exhibited higher activity with IC 50 value of 2.6 μg/ml than vitamin C, used as a positive control (IC50 value, 6.4 μg/ml) (Table IV). It was reported that compound 1, ampelopsin has protective effect on oxidant stress-induced apoptosis induced by H2O2 in MT-4 cells, antitumor effects, inhibitory effects on angiogenesis, and hepatoprotective activity (Murakami et al, 2004;Zeng et al, 2004;Luo et al, 2006;Ye et al, 2008). The results from free radical scavenging systems revealed that the ethyl acetate soluble fraction of S. koreana, and isolated compounds 1-3 may be useful for the treatment of various oxidative damage.…”
Section: Resultsmentioning
confidence: 99%